Hermeneutiese uitgangspunte in historiese Jesus navorsing: Metodologiese vooronderstellings - Geyser, P. A. (Hervormde teologiese studies, 2000)
Hermeneutical premises in historical Jesus research: Methodological presuppositions. The focus of this article is the presuppositions concerning the interpretation of the New Testament with reference to historical Jesus studies. Regarding the rhetorics of a text, communication conventions are discussed and applied to the concept "Kingdom of God". The concepts "situation" and "strategy" are investigated. "Situation" refers to the circumstances and aims of a writing. "Strategy" refers to the writer's persuasive techniques to bring the audience to appropriate action. The following social institutions of the audience should be taken into consideration: kinship, economy, politics and religion. Social-scientific criticism presupposes that both the social and historical disciplines are necessary for an adequate interpretation of ancient texts and their social contexts. The socio-historical approach investigates the intended meaning of texts, their Wirkungsgeschichte and relevance for the present-day reader.